Forensic Psychology / A Guide to Practice (Rouledge, 2000)
This book provides clear, detailed instructions on the basic skills, techniques and professional issues involved. Preface, Introduction, Survey's Into Psychological Evidence in Court, Ethical and Professional issues, The Roles of Forensic Psychologist, Psychological Testing, Psycholinguistic Techniques, Civil Cases, Criminal Cases, The Assessment and the Testimony: A Psychological Framework, Conclusions, Cases Cited, References, Index.